THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT ON INTENTION TO STAY IN THE RETAIL INDUSTRY IN JAKARTA - Sukistianingsih, Reni; Parimita, Widya; Wolor, Christian Wiradendi (Jurnal Comparative: Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of perceived organizational support, job satisfaction and organizational commitment on intention to stay in the Jakarta retail industry. In this study, using a quantitative approach, survey method and purposive sampling approach. The data analysis technique in this study used SPSS software version 26. The researcher sample used non-probability so that the sample size was 110 people. This study shows the results, (1) There is a positive and significant relationship between Perceived Organizational Support and Intention to Stay, (2) There is a positive and significant relationship between Job Satisfaction and Intention To Stay, (3) There is a positive and significant relationship between Organizational Commitment and Intention To Stay.